The Cambridge companion to Genesis - Arnold, Bill T. 1955- (Cambridge University Press, 2022)
Composition and structure of Genesis -- Social world of Genesis -- Themes and literary motifs of Genesis -- Reception history of Genesis
Includes bibliographical references and index
Keywords: Bibel -- Genesis; Ideengeschichte; Das Böse; Philosophie; Theodizee; Theologie; Übel; Bible / Genesis / Commentaries; RELIGION / Biblical Studies / Old Testament / General; Aufsatzsammlung